Research and Implementation of Optimization and Promotion of Power Grid Emergency Command Center - Xu Xiyuan; Liu Zeyu; Fang Diange; Cao Junxi; Ma Hongzhong (SHS Web of Conferences, 2023)
In order to enable the power grid emergency command center to meet the needs of the emergency work under the current new situation, and provide strong support for emergency response and important activities of power conservation, based on the in-depth study and analysis of the application scenarios and basic business of the power grid emergency command center, combined with advanced information communication technology, and studied the optimization and upgrading methods of the power grid emergency command center. Through the research on the optimization and upgrading method of power grid emergency command center, the optimization and upgrading scheme is proposed to guide the power grid enterprises to carry out the optimization and upgrading work of emergency command center. The optimization and upgrading scheme of the power grid emergency command center will be used for the transformation and upgrading of the emergency command center of the power grid companies at all levels, which will help the power grid companies at all levels to improve their emergency.